Avaliação dos impactos ambientais gerados pela energia eólica em terra e em mar aberto utilizando a matriz de Leopold - Luz, Clayton Diego da (2019)
Due to the high demand for electric energy in the last decades, investments in the energy area are necessary. However, the most usual means of production (hydroelectric, nuclear, thermoelectric) have high implantation and maintenance costs and imply large environmental impacts. Wind energy has been a major player in the field of investment in energy modals, due to the moderate cost and low environmental impact, but the onshore wind energy production presents numerous challenges regarding the availability of soil and the location to which it be implemented. In order to minimize several negative aspects of the onshore wind modality, a new modality of wind energy production has been developed, which in the last decade has been used in large scale by several European countries, the model of offshore wind), which consists of the installation of farms or wind farms on the seafront, which is credited with solutions to environmental and logistic problems presented by the onshore wind system, in addition to a greater capacity to generate electricity. Using a descriptive and quantitative study, this paper aims to determine if the assertion that the open ocean wind model has a lower environmental impact factor is true or false through the evaluation of the environmental impacts in each of the wind modalities using information taken from articles scientific, bibliographical and impact studies. Through this evaluation was determined the cause, moment and form that the impact acts in the physical, biological and socioeconomic environment. Based on this identification, it was possible to quantify the impacts using the Leopold Matrix, which enabled the measurement of the parameters Magnitude, Significance and Importance of each impact. The result of the measurement of these three parameters identified the open ocean wind modality as the modality with the lowest environmental impact. Thus the hypothesis that the open ocean wind modality has a lower environmental impact than the onshore modality is true.